In Pursuit of Sport Sustainability: Fund-Raising and the NCAA Division I Track and Field Core Product - Logan W. Roberts; Erianne A. Weight (Journal of Applied Sports Management, 2013)
National Collegiate Athletic Association (NCAA) Division I track and field programs have been a target of elimination in recent decades (Irick, 2011) as funds are often allocated to sports that provide the largest perceived potential return on investment (Marburger & Hogshead-Makar, 2003). Building on research that documents the influential role coaches can play in sport sustainability efforts (Cooper, 2012; Weight, 2010; Weight & Cooper, 2011), this study examines fund raising and fortification strategies of 111 Division I coaches through survey methodology. Important fund raising strategies emerged including communication with donors, maintaining an up-to-date contact database, and providing thank-you notes and/ or gifts to donors. Fortification strategies to enhance demand for collegiate track and field included decreasing the length of competitions and scoring regular season meets.
Keywords: College Sport; fundraising; track & field